Root and crown rot caused by Fusarium pseudograminearum in the euhalophyte Salicornia europaea: pathogenicity and mycotoxin production in plants grown in soilless culture - DELLI COMPAGNI, Emiliano; PARDOSSI, Alberto; PECCHIA, Susanna (Phytopathologia Mediterranea, 2025)
Salicornia europaea L. is a euhalophyte increasingly cultivated as a high-value green vegetable. In July 2021, root and crown rot occurred on 6-month-old S. europaea plants grown in peat-filled pots under a greenhouse, affecting 25% of plants. The causal agent was identified as Fusarium pseudograminearum O’Donnell & T. Aoki using morphological and molecular analyses. An experiment to assess the pathogenicity of this fungus to S. europaea was conducted with 96 seedlings in hydroponic culture. Half of these plants were inoculated with a conidial suspension of F. pseudograminearum. At 24 days post inoculation (dpi), half of the plants were transferred into a new hydroponic system, while the other plants were transplanted into pots. At 80 dpi, all inoculated plants grown in pots had shoot browning and desiccation symptoms, while these symptoms developed more slowly in 70% of the hydroponically grown inoculated plants. A qualitative symptom severity assessment scale showed that disease severity was greater (63%) in pot-grown plants than in hydroponically grown plants (46%). Fusarium pseudograminearum was consistently reisolated from diseased plants in both cultivation systems (62% from pots and 83% from hydroponics) fulfilling Koch’s postulates. Production of deoxynivalenol (DON) and zearalenone (ZEA) was investigated in vitro and in planta. Traces of DON (0.029 ± 0.012 mg kg-1) were found in severely damaged plants grown in hydroponics. In the in vitro test, F. pseudograminearum isolates from wheat crops in Spain (isolate ColPat-351) and Italy (isolate PVS Fu-7) were also assessed, and all tested isolates produced considerable amounts of ZEA. Fusarium pseudograminearum isolates obtained from S. europaea produced more DON (6.81 ± 0.24 mg kg-1, on average) than the Italian isolate PVS Fu-7 (0.37 ± 0.06 mg kg-1), while DON production by the Spanish isolate ColPat-351 was less than the limit of detection (< 0.25 mg kg-1). This is the first report of root and crown rot caused by F. pseudograminearum on S. europaea.